Penerapan Model Akuntansi Manajemen Pada UMKM Yang Bergerak Di Sektor Konveksi - Sakti Muda Nasution; Riri Rumaizha; Zen Munawar (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
Management accounting plays a crucial role in supporting decision-making, but its application in small businesses is often limited because the primary focus of record-keeping is on compliance with financial and tax regulations. This situation creates a problem of a lack of detailed information on cost structures, particularly overhead costs, making it difficult for business owners to control expenses and evaluate business unit efficiency. This study aims to design a simple, applicable, and appropriate management accounting model suited to the characteristics of small industrial businesses to provide relevant information for decision-making. The method used is a conceptual-analytical approach through a literature review, analysis of accounting practices in small businesses, and the design of a cost breakdown-based model, the establishment of cost centers and responsibility centers, the use of economic clearing sheets, and the preparation of managerial income statements. The main results indicate that this model can improve cost transparency, facilitate overhead allocation, and provide a contribution profit report that supports strategic decisions such as pricing, product prioritization, and cost control. A case study of a small garment factory demonstrates that the application of this model produces more detailed information, allows for evaluation of production unit efficiency, and increases profitability without requiring significant investment in an accounting system. In conclusion, management accounting can be simply adapted for small businesses by utilizing basic software, thereby strengthening the competitiveness, efficiency, and sustainability of businesses in facing market competition.